THE GLIMPSES OF INDIA'S FOREIGN POLICY IN THE WAKE OF THE COVID-19 - Ahmad Shairgojri, Aadil (RADJA PUBLIKA, 2022)
The Covid 19 pandemic affected people worldwide, and its effects continue to be felt today. The pandemic's impact and consequences vary depending on one's personal and social status. COVID-19 in India was a flop. An outbreak of coronavirus illnesses and deaths in 2021 plunged India into a humanitarian crisis. In order to reduce global vaccine inequity, India needs to use its world-renowned pharmaceutical manufacturing capabilities to provide COVID-19 vaccines to low-income countries. It should force India to rethink its domestic and foreign policies. With China's rise and India's national interests in a more dangerous world, the COVID-19 disaster forced India to rebuild its humanitarian reputation. This article contains in-depth information on the changes that have been implemented in India's foreign policy as a result of the COVID-19 pandemic.